Differentiation and characterization of osteoclasts from human induced pluripotent stem cells - Blümke, Alexander Felix; Simon, Jessica; Leber, Elizabeth; Scatena, Marta; Giachelli, Cecilia M. (JoVE. Video journal, 2024)
This protocol details the propagation and passaging of human iPSCs and their differentiation into osteoclasts. First, iPSCs are dissociated into a single-cell suspension for further use in embryoid body induction. Following mesodermal induction, embryoid bodies undergo hematopoietic differentiation, producing a floating hematopoietic cell population. Subsequently, the harvested hematopoietic cells undergo a macrophage colony-stimulating factor maturation step and, finally, osteoclast differentiation. After osteoclast differentiation, osteoclasts are characterized by staining for TRAP in conjunction with a methyl green nuclear stain. Osteoclasts are observed as multinucleated, TRAP+ polykaryons. Their identification can be further supported by Cathepsin K staining. Bone and mineral resorption assays allow for functional characterization, confirming the identity of bona fide osteoclasts. This protocol demonstrates a robust and versatile method to differentiate human osteoclasts from iPSCs and allows for easy adoption in applications requiring large quantities of functional human osteoclasts. Applications in the areas of bone research, cancer research, tissue engineering, and endoprosthesis research could be envisioned.